2022
DOI: 10.1111/jvim.16434
|View full text |Cite
|
Sign up to set email alerts
|

Impact of cytidine diphosphocholine on oxygenation in client‐owned dogs with aspiration pneumonia

Abstract: Background: New drugs for veterinary patients with acute respiratory distress syndrome (ARDS) are urgently needed. Early or late postinfection treatment of influenzainfected mice with the liponucleotide cytidine diphosphocholine (CDP-choline) resulted in decreased hypoxemia, pulmonary edema, lung dysfunction, and inflammation without altering viral replication. These findings suggested CDP-choline could have benefit as adjunctive treatment for ARDS in veterinary patients (VetARDS). Objectives: Determine if par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Compared to the previous reports evaluating markers of disease recovery in dogs with pneumonia or aspiration pneumonia, this cohort of dogs is an older population, with many of the dogs having a more complicated clinical course due to their concurrent systemic or focal neuropathy. [21][22][23][24][25][26]28,38 The studies to date have primarily focused on cohorts of younger dogs, with reported median ages ranging from 5 to 5.5 years, and of the combined total of 46 dogs studied, only three dogs were described to have concurrent GLOPP (n = 1) or megaoesophagus (2). 21,22,24 This study population therefore represents a subpopulation of dogs at risk for A-ILI that is not well represented in the recent studies investigating acute-phase protein monitoring in dogs with aspiration pneumonia.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Compared to the previous reports evaluating markers of disease recovery in dogs with pneumonia or aspiration pneumonia, this cohort of dogs is an older population, with many of the dogs having a more complicated clinical course due to their concurrent systemic or focal neuropathy. [21][22][23][24][25][26]28,38 The studies to date have primarily focused on cohorts of younger dogs, with reported median ages ranging from 5 to 5.5 years, and of the combined total of 46 dogs studied, only three dogs were described to have concurrent GLOPP (n = 1) or megaoesophagus (2). 21,22,24 This study population therefore represents a subpopulation of dogs at risk for A-ILI that is not well represented in the recent studies investigating acute-phase protein monitoring in dogs with aspiration pneumonia.…”
Section: Discussionmentioning
confidence: 99%
“…The dogs in this study had a median age of 12 years, with over half of the dogs (18 of 26) diagnosed with concurrent GOLPP or megaoesophagus as the underlying risk factor for an aspiration event. Compared to the previous reports evaluating markers of disease recovery in dogs with pneumonia or aspiration pneumonia, this cohort of dogs is an older population, with many of the dogs having a more complicated clinical course due to their concurrent systemic or focal neuropathy 21–26,28,38 . The studies to date have primarily focused on cohorts of younger dogs, with reported median ages ranging from 5 to 5.5 years, and of the combined total of 46 dogs studied, only three dogs were described to have concurrent GLOPP ( n = 1) or megaoesophagus (2) 21,22,24 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additional details of the clinical course, including radiographic evidence of aspiration, specific lung function markers (ratio of partial pressure of oxygen in the arterial circulation [PaO 2 ] to fraction of inspired oxygen [FiO 2 ][P:F ratio], oxygen saturation [SpO 2 ]), and outcome were also recorded. A diagnosis of aspiration pneumonia was made from a positive airway culture together with a clinical course of worsening lung function, indicated by hypoxaemia (P:F ratio ≤ 350 [ 13 ], or SpO 2 < 95% with FiO 2 ≥ 0.21), with or without thoracic radiographic evidence of aspiration pneumonia [ 14 , 15 , 16 ]. At the time of initial retrospective data collection the primary author (ST) interpreted all thoracic radiographs.…”
Section: Methodsmentioning
confidence: 99%